Research on asphalt pavement structure with cement treated large size macadam (CTB-50) base course. - Bentao Zhou; Yuan Yao; Xiaoke Geng; Yingjun Jiang; Tiezheng Guan; Ji Liang; Yue Wang (PLoS ONE, 2025)
Cement-treated large-size macadam base (CTB-50) has a high modulus, high strength, and good durability, which can increase the paving and rolling thickness, reduce the base layers, and enhance the overall structure of the pavement structure. However, there are no studies conducted on the mechanical response of asphalt pavement with a CTB-50 base course such that it can be promoted and applied in pavement engineering using CTB-50. This study analyzed the mechanical response and fatigue life of asphalt pavement structures with different base courses. Subsequently, the typical pavement structure form of asphalt pavement with a CTB-50 base course was recommended, and its effectiveness was verified through two highway engineering projects. The results showed that the base structure reduced from a three-layer CTB-30 base course structure to a two-layer CTB-50 base course structure, and the base layer bottom tensile stress of the asphalt pavement with CTB-50 base course is reduced by 5% compared to that of the asphalt pavement with CTB-30 base course. Based on the principle of equivalent fatigue life, the CTB-50 base layer thickness of the asphalt pavement can be reduced by approximately 6 cm compared to that of the CTB-30 base layer. The recommended pavement structure can reduce one layer in the construction of the base layer and improve the integrity of the asphalt pavement structure. The experimental road paved with the recommended CTB-50 base course pavement structure showed no evident pavement disease, whereas the road section with the CTB-30 base course showed early crack diseases in the asphalt pavement.